2019
DOI: 10.1104/pp.19.00766
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Activity of the Thylakoid H+/K+ Antiporter KEA3 Disturbs ∆pH-Dependent Regulation of Photosynthesis

Abstract: The thylakoid K 1 efflux antiporter 3 (KEA3) is required for regulating components of the proton motive force (pmf), proton concentration gradient (DpH), and membrane potential (Dc). The Arabidopsis (Arabidopsis thaliana) disturbed proton gradient regulation mutant (dpgr) is a dominant allele of KEA3, conferring disturbed transport activity. Here, we show that overexpressing the DPGR-type KEA3 (DPGRox) retarded plant growth, whereas overexpressing the wild-type KEA3 (KEA3ox) did not. In KEA3ox lines, the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…5). This is consistent with the fact that the contribution of KEA3 is not observed at high light intensities (Wang and Shikanai, 2019). The second phase is probably specifically observed at a relatively low light intensity, at which the transiently induced ∆pH-dependent downregulation is relaxed.…”
Section: Discussionsupporting
confidence: 89%
“…5). This is consistent with the fact that the contribution of KEA3 is not observed at high light intensities (Wang and Shikanai, 2019). The second phase is probably specifically observed at a relatively low light intensity, at which the transiently induced ∆pH-dependent downregulation is relaxed.…”
Section: Discussionsupporting
confidence: 89%
“…A dominant mutant allele of KEA3, disturbed proton gradient regulation (dpgr) , showed reduced non-photochemical energy quenching (NPQ) during induction of photosynthesis ( Wang et al., 2017 ). Overexpressing the DPGR-type KEA3 (DPGRox) inhibited plant growth, with disturbed ΔpH-dependent regulation of electron transport ( Wang and Shikanai, 2019 ). It was recently shown that AtKEA3 benefited photosynthesis and growth in chloroplast ATP synthase-compromised mutant, via a KEA3-dependent reduction of ΔpH ( Correa Galvis et al., 2020 ).…”
Section: Cpa2 Superfamilymentioning
confidence: 99%
“…It is interesting to point out that this difference emerged as a consequence of the illumination since it became detectable only if plants were exposed to light for more than 120 seconds (Figure 6B and Figure S7). This suggests that the alterations in pmf partitioning emerged as a result of modifications in the photosynthetic activity (Avenson et al, 2005; Wang and Shikanai, 2019). This difference between genotypes was again light intensity-dependent and using a stronger, fully saturating, illumination (1000 μmol photons m -2 s -1 ) mutants were indistinguishable from WT (Figure S8).…”
Section: Resultsmentioning
confidence: 99%